Peran Bimbingan Dan Konseling Dalam Menurunkan Tekanan Emosional Remaja Di Desa Karang Anyar Kecamatan Pegajahan - Sri Wahyuni; Ajeng Rindayu; Yurisna Yurisna; Fadira Al Mefa; Putri Novi Azhari (GUIDING WORLD (BIMBINGAN DAN KONSELING), 2023)
The aim of this research was to determine the role of guidance and counseling in reducing adolescent emotional stress. Emotional is a psychological condition experienced by almost all individuals. The emotional pressure experienced by teenagers in Karang Anyar Village, Pegajahan District is because teenagers are in difficult times or may be in a transitional period, both psychologically, physically, religiously and socially. This research uses a descriptive qualitative approach with case study research. Data was collected using interviews. The data technique used is Miles and Huberman analysis, the model is reduction, data presentation and drawing conclusions. And the research subjects in this research activity were 6 teenagers in Karang Anyar village, Pegajahan district who were experiencing emotional stress. The results of this research were conducted to provide guidance for concert or guidance counselors as a form of strategy to reduce emotional stress in adolescents. What is meant by Guidance Counseling is to focus more on support service activities for teenagers to overcome their problems.